2010
DOI: 10.3109/09593980903300470
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of muscle function and sensory perception measurements of the wrist extensors

Abstract: This study determined the reliability of muscle function and sensory perception measures of the wrist extensors. The test-retest reliability of the measurements was determined by an intraclass correlation coefficient (ICC), coefficient of variation (CV), standard error of measurements (SEMs), and one-way repeated measures ANOVA using the values collected from 25 young (20.6 +/- 1.3 years) healthy male volunteers on two occasions separated by 1 day. The measures consisted of grip strength, wrist extension stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
4
30
0
Order By: Relevance
“…Large variability of the CPT was also evidenced in subjects with spinal cord injury and neuropathic pain [29] . Khamwong et al [30] also found the similar result of greater in CV (i.e. 27 %) with the CPT measurement.…”
Section: Discussionsupporting
confidence: 52%
“…Large variability of the CPT was also evidenced in subjects with spinal cord injury and neuropathic pain [29] . Khamwong et al [30] also found the similar result of greater in CV (i.e. 27 %) with the CPT measurement.…”
Section: Discussionsupporting
confidence: 52%
“…As there is no information regarding this issue, we determined the clinical meaningfulness by estimating the minimally clinical important difference (MCID) using a distribution-based approach as recommended by Wells et al (2001). The findings demonstrated that all of these observed changes were beyond the standard error of measurements (Khamwong et al, 2010), and the observed values were greater than 37% (i.e., changes in thermal pain, pressure pain, range of motion, and strength were 6.2 C,42.4 kPa,11.4 ,29.5 N,respectively). Therefore, we considered that these amounts of change were clinically meaningful for rehabilitation and sport performance.…”
Section: Motor Functionmentioning
confidence: 88%
“…The same investigator conducted all measurements in a single-blinded manner. The room temperature was set at 25.0 C. All outcome measures including CPT, PPT, ROM (ROM-PF, ROM-PE, ROM-AF, ROM-AE) grip and wrist extension strength, were considered to be reliable with a 24-h interval of testretest (ICC > 0.85) (Khamwong et al, 2010).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Range of motion of shoulder flexion and abduction was recorded in degrees with the utilization of a standard goniometer. The reliability of a goniometer is shown with an intra-class correlation coefficient (ICC) of 0.95 by Khamwong and colleagues [29].…”
Section: Methodsmentioning
confidence: 99%